Work and Training Conditions of German Residents in Radiology – Results from a Nationwide Survey Conducted by the Young Radiology Forum in the German Roentgen Society - Oechtering, Thekla H.; Panagiotopoulos, Nikolaos; Völker, Martin; Lohwasser, Stefan; Ellmann, Stephan; Molwitz, Isabel; Storz, Corinna; Winther, Hinrich; Eisenblaetter, Michel; Antoch, Gerald; Schönberg, Stefan O.; Barkhausen, Jörg; Anton, Frank; Neumann, Stefan; Layer, Günter; Doerfler, Arnd; Koerber, Friederike; Wessling, Johannes; Wucherer, Michael; Raspe, Matthias (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose Good training is the basis for high job satisfaction and high-quality patient care in radiology. The aim of this survey was to record the current state of working conditions for residents in radiology training in Germany and to focus on the aspects of training and psychosocial workload. The description of the actual state should help to identify possible problem areas and to develop improvement approaches.Materials and Methods At the beginning of 2018, we sent an electronic questionnaire to the German Roentgen Society (DRG), the German Association of Chairmen in Academic Radiology (KLR), the Chief Physician Forum of the DRG (CAFRAD) and the Forum of Registered Radiologists (FUNRAD) with the request to forward it to radiology residents. With 63 questions, the questionnaire covered seven essential areas of medical working and training conditions. In order to ensure interdisciplinary comparability, most questions were identical to previous surveys among residents of other disciplines.Results 643 residents started the survey. 501 (78 %) questionnaires were fully processed and included in the final analysis. 65 % of respondents were satisfied with their current job situation. At the same time, shortcomings, especially with regard to the reconciliation of family and work as well as scientific and clinical work, became clear. Only 36 % of participants with children were satisfied with the compatibility of family and work at their workplace. Only 31 % of the researchers were satisfied with their research conditions. In addition, residents experienced a high psychosocial workload.Conclusion Job satisfaction is high among radiology residents in direct comparison to other disciplines. However, based on this survey, adjustments to working conditions and training in radiology seem necessary to maintain the health of the physicians concerned, to encourage motivation for scientific work and to enhance development opportunities, especially for women, through a better compatibility of work and family life. The present survey identifies strategies and leadership tools that can help to achieve this.Key Points: Residents in radiology training ...Citation FormatZiel Eine qualitativ hochwertige Weiterbildung ist Grundlage für eine hohe Arbeitszufriedenheit und eine exzellente Patientenversorgung in der Radiologie. Ziel dieser Umfrage war es, den aktuellen Stand der Arbeitsbedingungen von Ärzten in der Weiterbildung Radiologie in Deutschland zu erfassen und einen Fokus auf die Teilaspekte Weiterbildung sowie psychosoziale Arbeitsbelastung zu legen. Die Beschreibung des Ist-Zustandes soll helfen, mögliche Problemfelder zu identifizieren und Verbesserungsansätze zu entwickeln.Material und Methoden Anfang 2018 wurde ein elektronischer Fragebogen über die Deutsche Röntgengesellschaft (DRG) e. V., die Konferenz der Lehrstuhlinhaber für Radiologie (KLR), das Chefarztforum der DRG (CAFRAD) und das Forum Niedergelassener Radiologen (FUNRAD) an radiologische Weiterbildungsassistenten verschickt. Der Fragebogen deckte mit 63 Fragen 7 wesentliche Themenfelder ärztlicher Arbeits- und Weiterbildungsbedingungen ab. Um eine fächerübergreifende Vergleichbarkeit zu sichern, wurden Fragen von bisherigen Erhebungen unter Ärzten in Weiterbildung anderer Fachrichtungen übernommen.Ergebnisse 643 Ärzte haben die Umfrage begonnen. 501 (78 %) Fragebögen wurden vollständig bearbeitet und in die endgültige Analyse einbezogen. 65 % der Befragten waren mit ihrer derzeitigen beruflichen Situation zufrieden. Gleichzeitig wurden Defizite besonders in Bezug auf die Vereinbarkeit von Familie und Beruf sowie die Möglichkeit zu wissenschaftlichem Arbeiten deutlich. Nur 36 % der Teilnehmer mit Kindern waren zufrieden mit der Vereinbarkeit von Familie und Beruf an ihrem Arbeitsplatz. Nur 31 % der wissenschaftlich Tätigen waren zufrieden mit ihren Forschungsbedingungen. Zudem war die psychosoziale Arbeitsbelastung unter den befragten Ärzten stark ausgeprägt.Schlussfolgerung Die Arbeitszufriedenheit ist unter radiologischen Assistenzärzten im Vergleich zu anderen Fachrichtungen hoch. Dennoch scheinen auf Basis dieser Erhebung Anpassungen der Arbeits- und Weiterbildungsbedingungen in der Radiologie erforderlich, um die Gesundheit der betroffenen Ärzte zu erhalten, die Motivation für wissenschaftliches Arbeiten zu fördern und die Entwicklungsmöglichkeiten insbesondere von Frauen durch eine bessere Vereinbarkeit von Familie und Beruf aufzuwerten. Die vorliegende Umfrage zeigt Strategien und Führungsinstrumente auf, mit denen dies erreicht werden kann.Kernaussagen: Ärzte in radiologischer Weiterbildung ...Zitierweise
Keywords: ER-ratio; working conditions; psychosocial workload; continuing education; resident; radiology